The new monastics. - Byassee, Jason (Christian Century, 2005)
Features several Christian communities in the U.S. Background on the establishment of the Rutba House in Durham, North Carolina; Financial management practices of the members of the Reba Place Fellowship in Evanston, Illinois; Implications of overcoming pietism on the Church of the Servant King in Eugene, Oregon; Goal of the Celebration of Yahweh's Kingship event organized by the Church of Sojourners in San Francisco, California.